Gasification of binderless co‐pelletized hydrochars from banana leaves and coconut sawdust. (26th April 2022) - Ding, Lu; Yang, Mingming; Mosqueda, Alexander; Wang, Peiyao; Cheng, Xiaopeng; Medrano, Katleya
Summary: Residues from banana and coconut timber production offer potential advantages if used as solid fuel. This study investigated the gasification behavior of co‐pelletized, hydrothermally treated banana leaves (HBL) and coconut sawdust (HCS) at varied blend ratios. Pellet quality tests revealed that the individual and co‐pelletized HBL:HCS samples have excellent mechanical integrity. Their high compressive strengths, high mass densities, and low spring back effects likewise indicate their ability to form strong interparticle adhesion without the aid of external binders or modification of particle sizes. Although HCS showed slow char gasification conversion, co‐pelletization with HBL proved to enhance its reactivity. This improvement was due to HBL's significantly higher alkali index compared with HCS. Since increasing the HBL ratio increased the alkali index of the co‐pelletized samples, the pellet with the highest HBL ratio (HBL:HCS 3:1) showed the greatest reactivity enhancement. Gasification of the blended HBL and HCS pellets also produced a synergistic effect, which was most evident when the HBL ratio was lowest (HBL:HCS 1:3). The significant difference in the particle size of HBL and HCS, aggravated by increasing the HBL ratio, formed large interspaces that weakened the degree of synergy. Overall, findings revealed that mixed HBL and HCS can produce high‐quality pellets with enhanced gasification reactivity and synergistic effect. Novelty Statement: Gasification of binderless co‐pelletized hydrochars was proposed. Co‐pelletization showed high compressive strengths, high mass densities, and low spring back effects. Co‐pelletization of hydrochars enhanced gasification reactivity and synergistic effect. Abstract : Gasification of binderless co‐pelletized hydrochars was proposed. Co‐pelletization showed high compressive strengths, high mass densities, low spring back effects. Co‐pelletization of hydrochars enhanced gasification reactivity and synergistic effect.